(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article provides information on the history of the formation of madrasas in Central Asia, identifies the design methodology of 17th-century Bukhara architects, and based on this, a graphic reconstruction of the medical center "Madreseyi dor ush-shifo," built by the Bukhara Khan Subhankuli Khan in the 17th century, was developed. The original parameters of this building were determined in modern length measurements, and the proportional system of architectural shapes was identified.